189k views
3 votes
3u+9-8u=-31
simplify

2 Answers

2 votes

Answer:

u = 8

Explanation:

User Yorian
by
5.9k points
4 votes

Answer:

u=8

Explanation:

Greetings !

Given expression


3u + 9 - 8u = - 31

Group like terms of the expression


3u - 8u + 9 = - 31

Add similar elements


3u - 8u = - 5u

Thus,


- 5u + 9 = - 31

subtract 9 from both sides


- 5u + 9 - 9 = - 31 - 9

simplify


- 5u = - 40

then divide both sides of the expression by -5.


( - 5u)/( - 5) = ( - 40)/( - 5)

simplify


u = 8

Hope it helps!

User Jyunderwood
by
6.0k points